1993
DOI: 10.1097/00000658-199312000-00012
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Trial of Subxiphoid Pericardiotomy in the Diagnosis and Treatment of Large Pericardial Effusion A Follow-Up Report

Abstract: These data show that the cause of most large pericardial effusions can be determined by a thorough evaluation accompanied by subxiphoid pericardiotomy. In addition, subxiphoid pericardial biopsy and window creation is safe and effective in the treatment of these effusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 19 publications
2
11
0
2
Order By: Relevance
“…The complication rate was similar to that reported by Geissbuhler et al [12], however, higher than the reported in other series of thoracoscopy and subxiphoid intervention and may possibly reflect differences in the groups studied and the experience of the team with the procedure [13,14]. The intervention was effective in performing the diagnosis and treatment of pericardial effusions, and allows the accomplishment of associated pleural procedures.…”
Section: Discussionsupporting
confidence: 80%
“…The complication rate was similar to that reported by Geissbuhler et al [12], however, higher than the reported in other series of thoracoscopy and subxiphoid intervention and may possibly reflect differences in the groups studied and the experience of the team with the procedure [13,14]. The intervention was effective in performing the diagnosis and treatment of pericardial effusions, and allows the accomplishment of associated pleural procedures.…”
Section: Discussionsupporting
confidence: 80%
“…Effusion recurred in 8 patients in 2 mo and in 9 (16%) in the first year. In the subgroup of neoplastic pericardial effusion (n = 13), the mortality was 54% at 2 mo and 92% at 12 mo follow-up [74] . In a report of 67 patients (26 with cancer, 14 with neoplastic pericardial involvement) treated with subxiphoid pericardial drainage, the overall success rate was 82%, but the median survival was 393 d in cancer patients with negative cytology vs 122 d for those with malignant pericardial involvement.…”
Section: Surgical Treatmentmentioning
confidence: 97%
“…368 hastada uyguladıkla-rı subksifoid perikardiyal yaklaşımda nüks oranını işlemden bir ay sonra %10 olarak bildirmiştir [19]. Duke üniversitesinde yapılan prospektif bir çalış- mada değişik nedenlerle subksifoid perikardiyal pencere açılan hastaların %16'sında bir yıl içinde nüks oluştuğu rapor edildi [18]. Bizim çalışmamız-da bu yöntemin nüks oranı üç ay içinde %17,9 bulunmuş ancak gruplar arasında anlamlı bir farklılık saptanmamıştır.…”
Section: Sağkalım Analiziunclassified